Literature Review: Analysis of the Use of Concrete Media in Mathematics Learning in Elementary Schools Between 2019-2024 - Rozy, Shellawaty M.; Utanto, Yuli; Subali, Bambang; Ellianawati, Ellianawati (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the use of concrete learning media in mathematics learning at the elementary school level based on selected journal publications through a bibliometric approach using Scopus and Google Scholar databases published between 2019 and 2024. A total of 1,033 articles were initially identified during the search process, which were then filtered using inclusion and exclusion criteria, resulting in 54 relevant articles consisting of 53 from Google Scholar and 1 from Scopus. This research employed a literature review method with bibliometric analysis stages, including the identification of research trends, publication frequency, dominant keywords, and thematic developments related to concrete learning media in mathematics instruction. The findings indicate that the use of concrete media not only enhances students’ conceptual understanding of mathematics, but also contributes to increased learning motivation, critical thinking, creativity, and problem-solving skills. Moreover, concrete media are considered effective in creating a more interactive and meaningful learning environment for elementary school students. The results of this study are expected to serve as a reference for researchers and education practitioners interested in examining research trends concerning the use of concrete learning media in mathematics education and to provide direction for future research.